2009
DOI: 10.1074/jbc.m109.009126
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Ubiquitin Recognition by a Novel Domain from Human Phospholipase A2-activating Protein

Abstract: Ubiquitin (Ub) is an essential modifier conserved in all eukaryotes from yeast to human. Phospholipase A 2 -activating protein (PLAA), a mammalian homolog of yeast DOA1/UFD3, has been proposed to be able to bind with Ub, which plays important roles in endoplasmic reticulum-associated degradation, vesicle formation, and DNA damage response. We have identified a core domain from the PLAA family ubiquitin-binding region of human PLAA (residues 386 -465, namely PFUC) that can bind Ub and elucidated its solution st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Ub binding was confirmed using NMR HSQC experiments that showed specific chemical shift perturbations within 15 N-Ub in the presence of unlabelled His-tagged Doa1 β-Prp (Figure 1C and see Figure S1A available online). Quantifying chemical shift perturbations as a function of increasing Doa1 β-Prp concentrations indicated a K d of ~220 μM for mono-Ub (Figure 1D), a moderate affinity within the range of previously described UBDs (Dikic et al, 2009; Harper and Schulman, 2006; Hurley et al, 2006) and which is tighter than the >1 mM K d reported for the mammalian Doa1/Ufd3 PFU domain (Fu et al, 2009). Additional HSQC experiments were performed with 15 N-labeled Doa1 β-Prp, which showed a well-dispersed spectrum consistent with the predicted β-stranded propeller structure.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Ub binding was confirmed using NMR HSQC experiments that showed specific chemical shift perturbations within 15 N-Ub in the presence of unlabelled His-tagged Doa1 β-Prp (Figure 1C and see Figure S1A available online). Quantifying chemical shift perturbations as a function of increasing Doa1 β-Prp concentrations indicated a K d of ~220 μM for mono-Ub (Figure 1D), a moderate affinity within the range of previously described UBDs (Dikic et al, 2009; Harper and Schulman, 2006; Hurley et al, 2006) and which is tighter than the >1 mM K d reported for the mammalian Doa1/Ufd3 PFU domain (Fu et al, 2009). Additional HSQC experiments were performed with 15 N-labeled Doa1 β-Prp, which showed a well-dispersed spectrum consistent with the predicted β-stranded propeller structure.…”
Section: Resultsmentioning
confidence: 54%
“…The domains of Doa1 (Figure 1A) previously identified by homology and crystallographic studies include a C-terminal armadillo repeat domain (PUL; residues 465–715), a central PFU domain that binds Ub (320–450), and an N-terminal WD40 repeat-containing region predicted to form a β-Prp (residues 1–300) (Fu et al, 2009; Qiu et al, 2010). We performed a series of binding experiments using epitope-tagged fragments of Doa1 containing both the β-Prp and PFU domains or a fragment of the β-Prp alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural core (Rpt1) shows striking similarity to PFU, the PLAA family of Ubiquitin binding domain. PFU domain has been identified as an ubiquitin‐associated domain containing (α + β) topology . Currently, the exact function of either the PFU domain or other proteins with same or similar fold is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when 15 N-labeled Ub is titrated with unlabeled DC-UbP_N, it also causes chemical shift changes of the amide resonances of some residues on Ub [ Fig. 2(E UIM, 13 ZnF-UBP, 15 and PFU, 14 have been identified to bind specifically with Ub and its analogs with variable affinities within micromolar to millimolar scale. 4 Interestingly, SH3, a canonical domain binding with proline-rich motifs found in diverse signal transduction proteins, has also been identified to bind with Ub.…”
Section: Dc-ubp_n Can Bind With Ubmentioning
confidence: 99%